Expanding the evidence base for global recommendations on health systems: strengths and challenges of the OptimizeMNH guidance process. (December 2015) - Glenton, Claire; Lewin, Simon; Gülmezoglu, Ahmet
Abstract Background In 2012, the World Health Organization (WHO) published recommendations on the use of optimization or "task-shifting" strategies for key, effective maternal and newborn interventions (the OptimizeMNH guidance). When making recommendations about complex health system interventions such as task-shifting, information about the feasibility and acceptability of interventions can be as important as information about their effectiveness. However, these issues are usually not addressed with the same rigour. This paper describes our use of several innovative strategies to broaden the range of evidence used to develop the OptimizeMNH guidance. In this guidance, we systematically included evidence regarding the acceptability and feasibility of relevant task-shifting interventions, primarily using qualitative evidence syntheses and multi-country case study syntheses; we used an approach to assess confidence in findings from qualitative evidence syntheses (the Grading of Recommendations, Assessment, Development and Evaluation-Confidence in Evidence from Reviews of Qualitative Research (GRADE-CERQual) approach); we used a structured evidence-to-decision framework for health systems (the DECIDE framework) to help the guidance panel members move from the different types of evidence to recommendations. Results The systematic inclusion of a broader range of evidence, and the use of new guideline development tools, had a number of impacts. Firstly, this broader range of evidence provided relevant information about the feasibility and acceptability of interventions considered in the guidance as well as information about key implementation considerations. However, inclusion of this evidence required more time, resources and skills. Secondly, the GRADE-CERQual approach provided a method for indicating to panel members how much confidence they should place in the findings from the qualitative evidence syntheses and so helped panel members to use this qualitative evidence appropriately. Thirdly, the DECIDE framework gave us a structured format in which we could present a large and complex body of evidence to panel members and end users. The framework also prompted the panel to justify their recommendations, giving end users a record of how these decisions were made. Conclusions By expanding the range of evidence assessed in a guideline process, we increase the amount of time and resources required. Nevertheless, the WHO has assessed the outputs of this process to be valuable and is currently repeating the approach used in OptimizeMNH in other guidance processes.